2015
DOI: 10.1177/0886260515609582
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of Intimate Partner Abuse on Physical Health, Emotional Well-Being, and Problem Behaviors

Abstract: This study examines the physical health, emotional well-being, and problem behavior outcomes associated with intimate partner abuse (IPA) victimization and perpetration experiences by analyzing a nationally representative, prospective, and longitudinal sample of 879 men and women collected from the National Youth Survey Family Study (NYSFS) and assessed across a period of 9 years from 1993 to 2003. Using multivariate regression techniques, it was found that both men and women experience numerous negative outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…For example, Blake et al (2007) found that pregnancy happiness was more strongly correlated with the use of tobacco, drugs, and alcohol during pregnancy than pregnancy intentions were (see also Sable and Libbus 2000; Santelli et al 2009). This fits with other research showing how emotions shape various health behaviors (Simmons, Knight, and Menard 2018; Steptoe, Deaton, and Stone 2015). Therefore, pregnancy happiness may play a role in the causal chain linking health outcomes to their more distal social and contextual causes.…”
Section: Introductionsupporting
confidence: 92%
“…For example, Blake et al (2007) found that pregnancy happiness was more strongly correlated with the use of tobacco, drugs, and alcohol during pregnancy than pregnancy intentions were (see also Sable and Libbus 2000; Santelli et al 2009). This fits with other research showing how emotions shape various health behaviors (Simmons, Knight, and Menard 2018; Steptoe, Deaton, and Stone 2015). Therefore, pregnancy happiness may play a role in the causal chain linking health outcomes to their more distal social and contextual causes.…”
Section: Introductionsupporting
confidence: 92%
“…Due to this, research on aggression has increased considerably in recent years, studying its characteristics, prevalence, and consequences (Lee, 2016). The negative consequences of aggressive behavior are suffered by both the victims, including such problems as anxiety, depressive symptoms, relationship stability, or even psychiatric disorders (Crick & Bigbee, 1998;Cullerton-Sen et al, 2008;O'Moore & Kirkham, 2001;Simmons et al, 2018) and by the aggressors, who experience personal relationship problems or exhibit antisocial behaviors (Moffitt, 2006;Ostrov & Godleski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These include an increased risk of depression, anxiety, posttraumatic stress disorder (PTSD), and suicide (Bonomi et al, 2009; Devries, Mak, Bacchus, et al, 2013); back pain, abdominal or pelvic pain (Campbell, 2002), and poor sexual and reproductive health including dyspareunia, vaginal bleeding, unintended pregnancy, pregnancy termination, and irregular use of contraception (Bauleni et al, 2018; Coker, 2007; Hall et al, 2014; Maxwell et al, 2015). There is some evidence that IPV may be associated with greater body mass index (BMI), although findings have been inconsistent (Bosch et al, 2015; Mason et al, 2017; Simmons et al, 2018). Associations have also been reported between IPV and body shame and objectification (Gervais & Davidson, 2013) as well as altered eating behaviors (Bundock et al, 2013; Wong & Chang, 2016).…”
mentioning
confidence: 99%